2016
DOI: 10.1080/07435800.2016.1182185
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of thyroid hormone and thyrotropin receptors in reproductive tissues of adult female rabbits

Abstract: The wide presence of TRs and TSHR in female reproductive organs suggests varied effects of thyroid hormones and thyrotropin in reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The expression of TRα1‐2, TRβ, and TSHR in the distal urethra and the presence of specific TRH bindings sites at sacral level of spinal cord, including the Onuf's nucleus, support that thyroid actions clearly affect the neural circuits involved in the urethral closure of rabbits . In agreement, we have demonstrated herein that hypothyroidism affects urethral pressure, reducing its maximal pressure and increasing over 10‐fold the urethral resistance, among other outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TRα1‐2, TRβ, and TSHR in the distal urethra and the presence of specific TRH bindings sites at sacral level of spinal cord, including the Onuf's nucleus, support that thyroid actions clearly affect the neural circuits involved in the urethral closure of rabbits . In agreement, we have demonstrated herein that hypothyroidism affects urethral pressure, reducing its maximal pressure and increasing over 10‐fold the urethral resistance, among other outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that granulose and theca cells of primary, secondary, and tertiary follicles, as well as the stroma of the rabbit, express thyroid hormone receptors (TRs) and TSH receptors (TSHR) [33], a direct effect of thyroid hormones and TSH on this tissue could be assumed. In contrast to those studies in humans and animals in which hypothyroidism promotes the formation of cystic follicles [34, 35], we did not find more cystic follicles in hypothyroid rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The prostate is an accessory gland of the reproductive system, whose function is to produce an alkaline secretion that promotes the nutrition and survival of spermatozoa . Several studies have reported the presence of a prostate in women and female rodents . In gerbils, the female prostate presents structural homology with the ventral male prostate, making this a valuable model for comparative prostate studies…”
Section: Introductionmentioning
confidence: 99%